Choroidal effusion following continuous positive airway pressure treatment - Pornchai Simaroj (2018)
A 46-year-old man was diagnosed with obstructive sleep apnea and began using a nasal continuous positive airway pressure (CPAP) during sleep for a month. He presented with the complaint of a painful blurred vision in his left eye upon awakening two days earlier. His visual acuity was 20/25 both eyes. There was a mild anterior chamber reaction in the left eye. Fundus examination showed a localized choroidal effusion at the inferotemporal part of the left retina. The patient received topical 0.1% dexamethasone four times daily and temporarily discontinued the CPAP. By one week after treatment, the choroidal effusion was completely resolved.